The optimal pulse pressures for healthy adults with different ages and sexes correlate with cardiovascular health metrics - Chou, Chung-Hsing; Yin, Jiu-Haw; Lin, Yu-Kai; Yang, Fu-Chi; Chu, Ta-Wei; Chuang, Yuan Chieh; Lin, Chia Wen; Peng, Giia-Sheun; Sung, Yueh-Feng (Frontiers in Cardiovascular Medicine, 2022)
BACKGROUND: Pulse pressure (PP) may have a role in the development of cardiovascular disease and optimal PP for different ages and sexes remain to be determined. We studied subjects with favorable cardiovascular health (CVH) in a prospective cohort, proposed the mean PP as the optimal PP values and demonstrated its relationship with healthy lifestyles. METHODS AND RESULTS: A total of 162,636 participants (aged 20 years or above; mean age 34.9 years; 26.4% male; meeting criteria for favorable health) were recruited in a medical examination program between 1996 and 2016. PP in males was 45.6±9.4 mmHg and increased after the age of 50 years. PP in females was 41.8±9.5 mmHg and increased after the age of 40 years, exceeding that of males after the age of 50 years. We first show that PP increase correlates with both systolic blood pressure (BP) increase and diastolic BP decrease, except for females with PP of 40-70 mmHg. Individuals with mean PP values are more likely to meet health metrics, including body mass index (BMI) <25 kg/m2 (chi-squared =9.35, p<0.01 in males; chi-squared =208.79, p<0.001 in females) and BP <120/80mmHg (chi-squared =1300, p<0.001 in males; chi-squared =11000, p<0.001 in females). We propose a Health Score (Hscore) based on the sum of five metrics (BP, BMI, being physically active, non-smoking, and healthy diet), which significantly correlates with the optimal PP. CONCLUSION: The mean PP (within ±1 standard deviation) could be proposed as the optimal PP in the adult population with favorable CVH. The relationship between health metrics and the optimal PP based on age and sex was further demonstrated to validate the Hscore.